Rabies in Callithrix sp. in the urban area of Niterói, Rio de Janeiro, Brazil - Moutinho,Flavio Fernando Batista (2020)
Abstract In Brazil, rabies occurs mainly within an urban cycle, in which dogs and bats are reservoirs. This paper aims to report the occurrence of rabies in Callithrix sp. in Niterói, Rio de Janeiro, Brazil. In June 2019 a hybrid specimen was referred for diagnosis. The Direct Fluorescent Antibody, Mouse Inoculation, and Polymerase Chain Reaction tests were positive. A phylogenetic analysis was compatible with antigenic variant 3, characteristic of Desmodus rotundus. New studies should be undertaken to elucidate the real role of callitrichids in the urban rabies cycle.